Mapping Top Strategic E-commerce Technologies in the Digital Marketing Literature - Jallouli, Rim; Kaabi, Safa (Journal of Telecommunications and the Digital Economy, 2022)
The increasing use of e-commerce technologies has been studied in several fields and from different perspectives: technological, economic, organizational and social: hence, the need for a literature review that provides a map of top strategic e-commerce technologies from a managerial perspective and, more specifically, for digital marketing research. This paper aims to provide researchers with a comprehensive overview of the range of e-commerce technologies that have had a significant role in shaping digital marketing strategies. Based on a thematic analysis, e-commerce technologies were classified through eleven categories. The objective is to reveal how each set of technologies affected the different digital marketing strategies. Both descriptive and clustering analyses show that the most evoked technologies in the digital marketing literature are Information and Communication Technologies and platforms. Results outline the growing interest in artificial intelligence technologies. Moreover, this literature review reveals how digital marketing research has focused on technology-enabled segmentation and targeting strategies, along with the use of social platforms and the development of new products and services. The scarcity of marketing papers studying the impact of cloud technologies, IoT, blockchain and data analytics orient researchers towards exploring further the potential of these technologies for digital strategies.